Level of Public Speaking Anxiety and Coping Strategy Used by English Debaters at Unit Kegiatan Bahasa Asing in Dealing with English Debate - Prima Hidayoza; Zul Amri; Delvi Wahyuni (Universitas Negeri Padang, 2019)
An article under the titled “Level of Public Speaking Anxiety and Coping Strategy Used by English Debaters at Unit Kegiatan Bahasa Asing in Dealing with English Debate” aims at measuring and identifying level of public speaking anxiety, coping strategy, and correlation between level of PSA and coping strategy. Based on the need of this research, the subject of this research was 24 English department debaters at Unit Kegiatan Bahasa Asing, a legal English debating community in Universitas Negeri Padang. The instrument used was questionnaire, Personal Report of Public Speaking Anxiety (PRPSA), and anxiety coping strategy. The PRPSA was a self report to measure level of PSA, and it was adopted from McCroskey (1982). Moreover, anxiety coping strategy was a questionnaire to measure type of coping strategy, and it was adopted from Kondo and Yang (2004). Both of PRPSA and anxiety coping strategy consisted of 34 statements. The result shows that, English department debaters are generally categorised into moderate level of PSA, and peer seeking is a dominant coping strategy used to deal with anxiety. The SPSS was also used to analysed the correlation. It is pointed out that there is no significant correlation found between level of PSA and coping strategy.